Analisis Nilai Nilai Islam Dalam Strategi Pemasaran Dan Keuangan Perusahaan CV. Antique Production Untuk Mencapai Profitabilitas Yang Islami - Raudah Uci Mayasari Manik (Pusat Riset dan Inovasi Nasional, 2023)
The following research aims to provide information about marketing strategies consisting of product, price, place, whether promotions have been implemented. What we know so far is that every consumer has differences and reasons for consuming goods and services. From this statement, the company thinks about how to meet customer needs and desires, which then produces something that can provide awareness and a sense of interest to customers so they want to use or buy the services and products in question. The research method used is to use the description method, which is a type of research method that seeks to describe and clarify objects according to what they are. The results of this research explain that the implementation of marketing in CV. Antique Production has a strong influence on whether or not this business can develop and progress, still existing today, all of this can be seen from the efforts within the company itself. With the application of Islamic values ​​in the journey to build a business that is initiated and not without a daily leader and good teamwork at work. In Islamic economics, marketing or promotion is also applied to offer, inform and sell products or services on the market. By marketing or promoting, people will know about the existence of products and services.